Material and Development of Islamic Religious Education (PAI) Curriculum - Rahayu, Sri; Rohim, Azzizir; Hidayat, Syarif; Mustafiyanti, Mustafiyanti (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2024)
This paper aims to learn about the material and curriculum development of Islamic Religious Education (PAI). This research is library research. The data sources used are journals and books related to the material and PAI curriculum development. The methods (data analysis) used are deduction, induction, and comparative approaches. From this research, it can be concluded that development in the Islamic Religious Education (PAI) curriculum is interpreted as activities that produce the PAI curriculum. Learning material is one of the crucial things in teaching and learning activities. To design learning we need to think about what materials/learning materials are required to achieve learning objectives and achieve the desired competencies, that's why we need to develop learning materials. Curriculum content is material or teaching materials in the teaching and learning process, which includes knowledge, skills, and values related to the teaching materials delivered. The steps for developing curriculum content, in general, are to identify needs, Formulate curriculum objectives, Determine the cost budget, Form a development team, Compile the scope and sequence of teaching materials, and so on.